APLIKASI RESEP OBAT TRADISIONAL UNTUK MENGATASI ANEKA PENYAKIT BERBASIS ANDROID - Saputra, Firman Recky; Putri, Anggia Dasa (Computer Science and Industrial Engineering, 2021)
Most people in Batam now if they feel sick they always go to the pharmacy or hospital, even though before going to the hospital or pharmacy, people can treat themselves with traditional medicine, this is felt to be helpful for the community before going to the pharmacy or hospital. Even though the demand for traditional medicine in the Batam area is still high, the existing traditional medicine shops are very difficult or limited, this is felt as a problem for Batam residents who want to treat their illness with traditional medicine. Based on this, many residents are also looking for traditional recipes on the internet because they find it difficult to find traditional drug stores, but sometimes the source from the internet is sometimes unknown from where even most on the internet there are many fake recipes circulating that can harm the community. The method used in this study uses the RAD model, this research produces an android application for traditional medicine recipes.